Hands-On Application Development with PyCharm - Nguyẽ̂n Quân (Packt Publishing, 2019)
A definitive guide to PyCharm to help you build business-oriented Python applications ranging from modern web development to data science Key Features Learn basic to advanced PyCharm concepts to improve efficiency of your Python projects Work through practical examples that focus on efficient application development with PyCharm Explore advanced features in PyCharm such as code automation, version control, and GUI debugging Book Description JetBrain's PyCharm is the most popular Integrated Development Environment (IDE) used by the Python community thanks to its numerous features that facilitate faster, more accurate, and more productive programming practices. However, the abundance of options and customizations can make PyCharm seem quite intimidating. Hands-on Application Development with PyCharm starts with PyCharm's installation and configuration process, and systematically takes you through a number of its powerful features that can greatly improve your productivity. You'll explore code automation, version control, graphical debugging/testing, management of virtual environments, and much more. Finally, you'll delve into specific PyCharm features that support web development and data science, two of the fastest growing applications in Python programming. These include the integration of the Django framework as well as the extensive support for IPython and Jupyter Notebook. By the end of this PyCharm book, you will have gained extensive knowledge of the tool and be able to implement its features and make the most of its support for your projects. What you will learn Explore PyCharm functionalities and what makes it stand out from other Python IDEs Set up, configure, and customize your Python projects in PyCharm Understand how PyCharm integrates with Django for web development Discover PyCharm's capabilities in database management and data visualization Perform code automation, GUI testing, and version control in PyCharm Integrate interactive Python tools such as Jupyter Notebooks for building virtual environments Who this book is for If you're a beginner or an expert Python user looking to improve your productivity using one of the best Python IDEs, this book is for you. Basic knowledge of Python programming language is expected. Downloading the example code for this ebook: You can download the example code files for this ebook on GitHub at the following link: https://github.com/PacktPublishing/Hands-on-Application-Development-with-PyCharm ...